Exploring clinical communication in a teaching hospital in Ghana. Issue 2 (22nd May 2019) - Abor, Patience Aseweh
Abstract : Purpose: The purpose of this paper is to investigate the clinical communication using Tamale Teaching Hospital as a case. Design/methodology/approach: The paper is based on the Reassure, Explain, Listen, Answer, Take Action and Express Appreciation (RELATE) model and the Four Habits models of Clinical Communication. Findings: The results of the study indicate that leadership conducted staff meetings with some of the components of the RELATE model. These include staff meetings, employee rounding and communication/notice boards. The results of the study also suggest that much as some parts of the Four Habits model was used in provider–patient communication, certain aspects of the model were absent. The study identified some communication challenges including poor dissemination, lack of unity among some health workers, poor attendance in meetings and, with respect to patients, language barrier, patients' reluctance to disclose their actual health problems to health providers, lack of privacy and lack of a friendly environment. Practical implications: Providers, especially physicians, should be given training on the local languages in areas where they perform their services. Health service providers should receive as part of their learning in-depth training on the Four Habits model of Clinical Communication, especially the Medical Officers. Originality/value: It is imperative to embrace evidence-based practices/models aimed at securing proper communication in all hospitals but most especially teaching hospitals.